MicroRNA expression profiles of stress susceptibility and resilience in the prelimbic and infralimbic cortex of rats after single prolonged stress - Huang, Gengdi; Iqbal, Javed; Shen, Dan; Xue, Yan-xue; Yang, Mei; Jia, Xiaojian (Frontiers in Psychiatry, 2023)
The experience of traumatic stress can engender lasting memories associated with the trauma, often resulting in post-traumatic stress disorder (PTSD). However, only a minority of individuals develop PTSD symptoms upon exposure. The neurobiological mechanisms underlying the pathology of PTSD are poorly understood. Utilizing a rat model of PTSD, the Single Prolonged Stress (SPS) paradigm, we were able to differentiate between resilient and susceptible individuals. Fourteen days after the SPS exposure, we conducted the behavioral analyses using Elevated Plus Maze (EPM) and Open Field (OF) tests to identify male rats as trauma resilient or susceptible. We focused on the microRNA (miRNA) profiles of the infralimbic (IL) and prelimbic (PL) cortical regions, known to be crucial in regulating the stress response. Our investigation of stressed rats exposed to the SPS procedure yielded divergent responses, and differential expression microRNAs (DEmiRs) analysis indicated significant differences in the IL and PL transcriptional response. In the IL cortex, the GO analysis revealed enriched GO terms in the resilient versus control comparison, specifically related to mitogen-activated protein kinase and MAP kinase signaling pathways for their molecular functions as well as cytosol and nucleoplasm for the biological process. In the susceptible versus resilient comparison, the changes in molecular functions were only manifested in the functions of regulation of transcription involved in the G1/S transition of the mitotic cell cycle and skeletal muscle satellite cell activation. However, no enriched GO terms were found in the susceptible versus control comparison. In the PL cortex, results indicated that the DEmiRs were enriched exclusively in the cellular component level of the endoplasmic reticulum lumen in the comparison between resilient and control rats. Overall, our study utilized an animal model of PTSD to investigate the potential correlation between stress-induced behavioral dysfunction and variations in miRNA expression. The aforementioned discoveries have the potential to pave the way for novel therapeutic approaches for PTSD, which could involve the targeted regulation of transcriptome expression.